2020
DOI: 10.1016/j.amsu.2020.07.031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol and marijuana on survival after severe traumatic brain injury: A retrospective cohort study

Abstract: Background Alcohol (ETOH) and marijuana (THC) use have previously shown to improve outcomes after Traumatic Brain Injury (TBI). However, whether TBI severity impacts outcomes among patients tested positive for both ETOH and THC remains unclear. Materials and methods A retrospective review from the Northern Ohio Regional Trauma Registry, which includes deidentified data from six regional hospitals, including three Level 1 and three Level 3 trauma centers, was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Early intubated patients were more likely to have a GCS score of 7 (53.4% vs. 40.5%, p < 0.001) and a positive toxicology screen for illegal drugs (26.5% vs. 20.2%, p = 0.001), and also sustained more severe head injuries (p < 0.001). The respiratory rate on admission was similar between the two groups (18 [15][16][17][18][19][20][21][22] in the immediate intubation group vs. 18 [16][17][18][19][20][21] in the delayed/no intubation group, p = 0.356), whereas the oxygen saturation was higher in the immediate intubation group (99% [96-100%] vs. 98% [96-100%], p = 0.008). The overall mortality was 18.7% in patients with an immediate intubation, compared with 15.6% in patients with a delayed or no intubation (p = 0.046).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Early intubated patients were more likely to have a GCS score of 7 (53.4% vs. 40.5%, p < 0.001) and a positive toxicology screen for illegal drugs (26.5% vs. 20.2%, p = 0.001), and also sustained more severe head injuries (p < 0.001). The respiratory rate on admission was similar between the two groups (18 [15][16][17][18][19][20][21][22] in the immediate intubation group vs. 18 [16][17][18][19][20][21] in the delayed/no intubation group, p = 0.356), whereas the oxygen saturation was higher in the immediate intubation group (99% [96-100%] vs. 98% [96-100%], p = 0.008). The overall mortality was 18.7% in patients with an immediate intubation, compared with 15.6% in patients with a delayed or no intubation (p = 0.046).…”
Section: Resultsmentioning
confidence: 91%
“…15,16 The evidence from clinical studies remains controversial, with some studies showing a lower mortality associated with alcohol consumption, [17][18][19][20][21] and others showing no effect. 22,23 Furthermore, head AIS, GCS score of 7, tachycardia, and younger age were identified as independent clinical factors associated with intubation. These factors could potentially be taken into account to formulate a more selective approach to immediate intubation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tohme et al [ 68 ] showed that GCS < 9 in emergency department, abnormal pupil reaction, and ISS ≥ 25 were factors associated with mortality at 14 days after severe TBI (Abbreviated Injury Scale score of head region > 3). Likewise, in the Leskovan study et al [ 73 ], age, ICU, GCS, ISS, LOS (day) are factors associated with mortality in patients those patients, however, the use of blood alcohol content was not a significant predictor of mortality at discharge. Finally, Bonow et al was also able to show in his study in Latin America that the location for the patient treatment was also related with their outcome [ 3 ].…”
Section: Discussionmentioning
confidence: 91%